Risk Factors for Hearing Loss in High-risk Neonates at a Tertiary Care Centre in Central India: A Prospective Observational Study - Leena Dhande; Prerana Ganaboor; Rasika Hattewar; Chetan Jaiswal (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: Hearing impairment and deafness are global issues that affect 5% of the world's population, with nearly 34 million children requiring rehabilitation to address their Hearing Loss (HL). An approximately 10-20 fold higher incidence of audiological risk factors has been noted in Neonatal Intensive Care Units (NICUs), which translates that 2-5% of all newborns in NICUs may be affected. Early diagnosis of HL and intervention can be advantageous from the timely fitting of hearing aids or cochlear implants. Aim: The aim of this study was to evaluate the risk factors for HL in NICUs and Special Neonatal Care Units (SNCUs) at a tertiary care hospital in Central India. Materials and Methods: This prospective, observational, single-centre study was conducted from October 2019 to September 2021 in the Department of Paediatrics at Indira Gandhi Government Medical College and Hospital, Nagpur, Maharashtra, India. A total of 319 neonates at high-risk for HL, discharged from NICUs and SNCUs, were included in the study. The association between risk factors like prematurity, Low Birth Weight (LBW), Toxoplasmosis, Rubella, Cytomegalovirus, Herpes Simplex (TORCH) infections, neonatal asphyxia, neonatal sepsis, meningitis, exchange transfusion, assisted ventilation, and HL were studied. The chi-square test was used to assess the association between SNHL and risk factors. Results: The incidence of Sensorineural Hearing Loss (SNHL) was 3.76%. Neonatal asphyxia (p-value <0.01), exchange transfusion (p-value <0.001), TORCH infections (p-value <0.001), meningitis (p-value <0.001), and assisted ventilation (p-value <0.001) were found to be significant risk factors associated with SNHL. Conclusion: Based on the assessment of risk factors, it was concluded that neonates should undergo hearing screening tests within the first month of life, and a diagnosis should be made by three months of age. This allows specialists to initiate treatment and intervention by six months of age, helping children with impaired hearing avoid the harmful consequences of semantic deprivation.